2018
DOI: 10.3389/fphys.2018.00005
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Proteins and Melatonin Receptors in Neurons and Glia of the Sapajus apella Cerebellum

Abstract: Oscillations of brain proteins in circadian rhythms are important for determining several cellular and physiological processes in anticipation of daily and seasonal environmental rhythms. In addition to the suprachiasmatic nucleus, the primary central oscillator, the cerebellum shows oscillations in gene and protein expression. The variety of local circuit rhythms that the cerebellar cortex contains influences functions such as motivational processes, regulation of feeding, food anticipation, language, and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Arrhythmic animals with SCN lesions, however, no longer exhibit rhythmic clock gene expression, suggesting that the SCN and cerebellum have a hierarchical relationship (Rath et al., ). As there are no direct connections from the SCN to the cerebellum, the mechanism by which circadian rhythmicity in the cerebellum is entrained to the SCN or the LD cycle is unknown; however, several studies have hypothesized some form of hormone signaling (Guissoni Campos et al., ; Mendoza et al., ; Mordel et al., ). Interestingly, clock gene expression is localized to granule cells and Purkinje cells in mice (Rath et al., ).…”
Section: Metencephalon (Hindbrain): Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhythmic animals with SCN lesions, however, no longer exhibit rhythmic clock gene expression, suggesting that the SCN and cerebellum have a hierarchical relationship (Rath et al., ). As there are no direct connections from the SCN to the cerebellum, the mechanism by which circadian rhythmicity in the cerebellum is entrained to the SCN or the LD cycle is unknown; however, several studies have hypothesized some form of hormone signaling (Guissoni Campos et al., ; Mendoza et al., ; Mordel et al., ). Interestingly, clock gene expression is localized to granule cells and Purkinje cells in mice (Rath et al., ).…”
Section: Metencephalon (Hindbrain): Cerebellummentioning
confidence: 99%
“…Interestingly, clock gene expression is localized to granule cells and Purkinje cells in mice (Rath et al., ). In primates, however, PER1/2‐ir is expressed in the Purkinje cell layer (the primary output of the cerebellum), but not the granule or molecular cell layers, with higher expression during the day (ZT 10) compared to the night (ZT 19; Guissoni Campos et al., ). Bmal1 deletion specifically in granule cells renders expression of the majority of clock genes arrhythmic; however, circadian locomotor behavior is not significantly changed (Bering, Carstensen, & Rath, ).…”
Section: Metencephalon (Hindbrain): Cerebellummentioning
confidence: 99%
“…Luciana Pinato’s study showed that cerebellar can synthesize melatonin as a response to inflammation ( 23 ). Guissoni Campos, L. M. et al reported that the effects of melatonin on cerebellum may be related to sensorimotor and neuroprotection ( 60 ). It should be mentioned that melatonin is a neuroprotective drug when cerebellar cells are attacked.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of rhythmicity does not rule out these receptors like targets in treating diseases involving the ION ( Stankov et al, 1994 ; Fraschini et al, 1999 ). Previously, these receptors had already been described in the cerebellum, another area known to be involved in motor control ( Mazzucchelli et al, 1996 ; Guissoni Campos et al, 2018 ). The presence of these receptors in this nucleus reinforces the possible melatonin participation in controlling circadian phenomena subserving motor performance ( Stankov et al, 1994 ), in addition to other functions already described ( Reiter et al, 2012 ; Cipolla-Neto et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, little was described as melatonin receptors and their relationship with clock genes in brain areas related to motor functions. Both receptors and clock genes were found in the cerebellum ( Guissoni Campos et al, 2018 ), where the maximal expression of melatonin receptors was found to coincide with that of Per proteins, base nuclei, and the substantia nigra ( Uz et al, 2003 , 2005 ; Christiansen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%